Answer:
a = -66
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtract Property of Equality
Explanation:
Step 1: Define
13 + a/11 = 7
Step 2: Solve for a
- Subtract 13 on both sides: a/11 = -6
- Multiply 11 on both sides: a = -66
Step 3: Check
Plug in a into the original equation to verify it's a solution.
- Substitute in a: 13 - 66/11 = 7
- Divide: 13 - 6 = 7
- Subtract: 7 = 7
Here we see that 7 does indeed equal 7.
∴ a = -66 is the solution to the equation.